EFFECT OF POROSITY ON COMPRESSIVE STRENGTH OF POROUS NiTi ALLOY FABRICATED BY POWDER METALLURGY - Kaya, Mehmet; Orhan, Nuri; Somunkiran, Ilyas (Gazi Univ, Fac Engineering Architecture, 2008)
Porous NiTi alloy samples to be used as implant material were synthesized in different porosities through a powder metallurgical method, self-propagating high-temperature (SHS) synthesis. The powder blend composing Ni and at%49.5Ti was mixed 24 hours and cold pressed under different pressures. The green compacts were heated in a furnace up to 200 degrees C under a high purity argon gas protective atmosphere and then ignited by applying a high electrical voltage. It was found that open and closed cell pores formed in different percentages and shapes. In addition; increasing cold compaction pressure applied reduced the porosity levels and increased the compressive strength of the porous compacts synthesized.
Keywords: Porous NiTi; powder metallurgy; SHS; compressive strength; implant material